Industrial training at Information Resource Center of Campus Sultan Haji Ahmad Shah (KSHAS IRC) / Nurul Najihah Mat Arif - Mat Arif, Nurul Najihah (Bachelor Degree of Information Science (Hons.) Library Management, 2022)
This report describes and explains all my activities during my internship training at KSHAS IRC within 23 weeks in order to complete my degree courses. I have started this internship training from pt September 2021 and ended on 3 pt January 2022. Universiti Tenaga Nasional (UNITEN) is a private university wholly-owned by Tenaga Nasional Berhad (TNB). The University which is one of the Government Linked Universities (GLUs) in Malaysia operates two campuses which one main campus in Putrajaya and the other is in Bandar Muadzam Shah, Pahang. In KSHAS IRC, I have experienced new tasks and work environment. This is my first experience working in library environment. At the beginning of my internship, I felt a little bit nervous and difficult to adapt with the new environment. From time to time, thanks to Allah because I managed to adapt with the new kind of working environment. My supervisor gives me a variety of task in order to train me to be a better worker for the future. While doing the task, I realize that many staff in this library are very helpful and always guide me to complete the task neatly and nicely. As a human being, I admit that I always make mistakes. But staff in this library always give their hands in I faced any problems. This can be considered as my preparation for me before start my career path.